Pengaruh Jenis Mulsa Organik terdahap Pertumbuhan dan Hasil Tanaman Kacang Tanah - Diputra, I Made Martana; Rai, I Nyoman; Santosa, I Gusti Ngurah (Agrotrop : Journal on Agriculture Science, 2023)
The Effect of Organic Mulch Types on Growth and Production of Ground Peanuts. The condition of agricultural land in Bali which is starting to decrease due to the conversion of land to non-agricultural purposes has resulted in land optimization being urgently needed so that food needs can still be fulfilled. Land optimization can be carried out on potential dry lands and which have not been widely developed. In Bali, Subak Abian is an area to develop agriculture in dry land but mostly to obtain perennial plants produce so there are no many annual plants are cultivated. Based on this, to meet the needs of food diversification can be carried out by optimizing the dry land, introducing ground peanuts as annual crop and using the application of mulch as an alternative method of overcoming water problems in dry land. This research was conducted with the aim of knowing the effect of applying organic mulch on growth and yield ground peanuts in dry lands. This research was conducted at Subak Abian Tirta Taman Sari Tanah Ayu, Sibang Gede Village, Abiansemal District, Badung Regency, Bali and several variables were carried out at the Laboratory of Agronomy and Horticulture and Soil Environment Science, Faculty of Agriculture, Udayana University. This study used randomized block design with organic mulch treatment consisting of three levels, M 0 , M 1 , M 2 . The results showed ground peanuts on the M 2 treatment significantly gave the highest yield to the variable number of pods (17,61 pods), fresh stover weight (194,72 g) and dry stover weight (46,62 g).